Effects on Structural and Optical Properties of PMMA by Integration with Cu Nanoparticles - Alisha; Garg, D. (Journal of Scientific Research, 2024)
Cu-PMMA nanocomposite films have been prepared via ex-situ chemical route by reduction of cupric chloride dissolved in aqueous CTAB solution with hydrazine and then incorporated the prepared Cu nanoparticles in a solution of Polymethylmethacrylate (PMMA) in chloroform and cast into thin films. Optical and structural characterizations of resulting nanocomposite films were performed using UV-visible spectroscopy and Transmission Electron Microscopy (TEM). Characteristic Surface Plasmon Resonance (SPR) peak of Cu nanoparticles was observed at about 2.14 eV (577 nm) in absorption spectra of Cu-PMMA nanocomposite films. From the observation of absorption spectra, the optical band gap and Urbach’s energy values have been calculated. Band gap values of Cu-PMMA nanocomposite films were found to decrease from 3 eV to 2.4 eV, while Urbach’s energy values increased with the increase in the concentration of Cu nanoparticles in PMMA. The decrease in the optical band gap and increase in Urbach’s energy values indicated the modifications in the optical band structure of the PMMA matrix on the incorporation of Cu nanoparticles. TEM micrograph revealed spherical Cu nanoparticles embedded in PMMA with an average diameter of 6.5+ 2.5 nm.